Against the stream: Antidepressants are not antidepressants – an alternative approach to drug action and implications for the use of antidepressants. (30th January 2018) - Moncrieff, Joanna
Summary: Although antidepressants are regarded as effective and specific treatments, they are barely superior to placebo in randomised trials, and differences are unlikely to be clinically relevant. The conventional disease-centred understanding of drug action regards antidepressants as targeting an underlying brain process, but an alternative 'drug-centred' view suggests they are psychoactive substances that modify normal mental states and behaviour. These alterations, such as numbing of emotions, may reduce feelings of depression, and also create amplified placebo effects in randomised trials. Patients should be informed that there is no evidence that antidepressants work by correcting a chemical imbalance, that antidepressants have mind-altering effects, and that evidence suggests they produce no noticeable benefit compared with placebo. Declaration of interest: The author is co-chairperson of the Critical Psychiatry Network.